Capital account policies in emerging Asian economies: Are they effective in the 2000s? - Juthathip Jongwanich (Asian Development Bank (ADB), 2019)
This paper examines the effectiveness of capital account policy in terms of its ability to affect the volume and composition of capital flows, relieve pressures on real exchange rates, and foster monetary policy independence. Ten emerging Asian economies are used as case studies to assess the effectiveness of capital account policy during 2000−2015. The results suggest that some types of capital controls are effective in reducing the volume of capital flows and pressure on real exchange rates. The choice of exchange rate regime matters in terms of the effectiveness of capital controls for fostering monetary policy independence. Although some types of capital controls are effective in creating macroeconomic stability, implementing capital account policy needs to be undertaken with caution. This is because substitution or complementarity among capital controls is evident, both within and across countries in the region. It seems that strong economic fundamentals are more important than capital account policy for changing the composition of capital inflows toward more stable and long-term flows.
Keywords: F32; F31; O53; 330; capital flows; capital restrictions; emerging Asia